ANALISIS PENERAPAN SELF QUALITY MANAGEMENT PADA LEMBAGA KEUANGAN SYARIAH - Diva Ananda Dinanti; Ahmad Hazas Syarif (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to describe the implementation of Self Quality Management (SQM) in Islamic Financial Institutions. The current development in the Islamic Finance industry is experiencing rapid progress, leading to increasingly intense competition. This situation necessitates Islamic financial intitutions to enchance the quality of services provided in order to remain competitive. The method employed in this research is qualitative, utilizing a literature study approach. The findings of this study indicate that the implementation of SQM plays a crucial role in improving quality and performance in accordance with Islamic Principles. SQM not only cultivates individuals who are technically competent but also forters spiritual integrity and morality.